Latex sensitivity among hospital employees and atopic children - Saraçlar, Yıldız; Çetinkaya, Feyzullah; Tuncer, Ayfer; Şekerel, Bülent; Hovanec Burns, Debra; Ünver, Ercan (The Turkish Journal of Pediatrics, 1998)
Allergic reactions to latex products are an important health problem for health care workers and children. To investigate the prevalence of latex and latex-associated food sensitivities among hospital employees and atopic children, 61 hospital employees (44 nurses, 13 cleaning staff, 4 technicians) and 40 atopic children were evaluated by in vivo and in vitro testing methods. All subjects were also skin prick tested with common inhalant allergens and some cross-reactive food allergens to latex. In addition, all subjects were evaluated using an enzyme-linked immunometric assay for detection of specific IgE to inhalant allergens and to the known food latex cross-reactant food allergens (banana, chestnut, peanut and kiwi fruit). Latex challenges were performed in 12 history-negative and anti-latex IgE positive atopic children. Seven of the 61 hospital staff (11.4%) and four of the 40 atopic children (10%) showed skin reactivity to latex. By serologic testing, hypersensitivity to latex was found in 30 subjects, to banana in 23, to chestnut in 37, to peanut in 32, and to kiwi fruit in 22 subjects. Latex challenges were negative in all of the children who were tested. Total IgE was higher than expected in 32 subjects and 50 individuals tested positive for specific IgE to common inhalant allergens (AlaTOP). These results indicate that latex allergy may be a health problem for our hospital staff and atopic children. In vitro testing may detect latex-specific IgE in atopic children even when no history of an adverse reaction to latex is present.